AL-QUR’AN INSIGHTS ABOUT KIZB - Syamsuddin, Syamsuddin; Abubakar, Achmad; Galib, M.; Sohrah, Sohrah (Jurnal Diskursus Islam, 2021)
This research is related to the comprehensive view of the Qur’an about kiz|b, the discussion focuses on matters related to kiz|b, namely the essence of kiz|b: definitions and terms that are relevant in meaning to kiz|b either directly or indirectly. , explicitly or implicitly designated by the Qur’an, including, subject, object, motive and impact This research is (library research), intended to obtain data and information, literature in the form of books, notes and reports of scientific research that done before. These written data were then analyzed qualitatively. This is done because this research departs from the exposure of research data in the form of verses of the Qur’an, then put forward various interpretations related to the verse referred to by using various approaches. Then this research will offer a theory about the insight of the Qur’an about kiz|b. This type of research is classified as descriptive qualitative research, which can be interpreted as a problem solving procedure that is being studied by carefully describing or describing the state of the object of research. This descriptive research is a method designed to collect data and information whose main purpose is to provide a clear picture of the nature of a situation. Because this research is descriptive, it is not intended to test existing theories, but is directed to develop theories and ideas related to الكذب which can be interpreted as a problem solving procedure that is being studied by describing or describing the state of the object of research carefully. This descriptive research is a method designed to collect data and information whose main purpose is to provide a clear picture of the nature of a situation. Because this research is descriptive, it is not intended to test existing theories, but is directed to develop theories and ideas related to الكذب which can be interpreted as a problem-solving procedure that is being studied by carefully describing or describing the state of the object of research. This descriptive research is a method designed to collect data and information whose main purpose is to provide a clear picture of the nature of a situation. Because this research is descriptive, it is not intended to test existing theories, but is directed to develop theories and ideas related to الكذب في الان al-kiz|b fi al-Qur’an Insight of al-Qur’an about Kiz|b, the approach in question is the approach to the science of interpretation, namely the science by which an understanding of the Qur’an is obtained. This research data comes from a lot of literature, so this research uses documentary data collection techniques, namely finding and collecting data sourced from written sources such as primary and secondary data obtained from the Qur’anic manuscripts, hadith books, interpretation books and other literature related to the discussion of research, the object of this research is the verses of the Qur’an about al-Kiz|b whose data is classified as qualitative data, then the data is analyzed using content analysis techniques.